Value Engineering In Planning Construction of Ampelsari Reservoir Pasuruan Regency - Umarwoko Daniarto, Cornelius; Oetomo, Wateno; Wulandari, Esti (Green Publisher Indonesia, 2022)
Controlling the cost and time of project implementation is important in a project management process. In this research, a value engineering analysis will be carried out on the Ampelsari Reservoir construction plan to determine the most effective and cost-efficient alternative construction design. The application of value engineering to determine the amount of construction cost savings with a work plan includes: Information Stage, Creative Stage, Analysis Stage, and Recommendation Stage. The results of the value engineering analysis in this study obtained construction cost savings of Rp. 1,624,162,703.65 or 6.16% of the total initial design cost, with alternative designs selected in 3 (three) types of work, on Spillway Work with K-225 Reinforced Concrete and Cyclop Concrete work items (A3), on Gate Valve House Work with Concrete Rebate and U-Ditch 30 x 30 work items (B3), on Reservoir Work with HDPE Pipe work items dia. 2.5